Digital resources and learning outcomes in college physical education: a survey study - Yu, Jingnan; Song, Wenlong (Institute of Advanced Engineering and Science, 2025)
The effectiveness of digital resources in teaching remains a widely debated issue, particularly in the field of physical education. This article aims to examine the impact of digital resource learning on the learning outcomes of undergraduate physical education courses, with a specific focus on the role of students’ awareness and competence in using digital resources. Using a questionnaire survey method, the study analyzed data from 310 undergraduate students from five universities in China. The results showed that digital use ability, use awareness and resource environment had a significant positive effect on satisfaction with learning outcomes. Digital usage awareness fully mediated the effect of digital learning confidence on learning outcome satisfaction and partially mediated the effect of digital usage ability and resource environment on learning outcome satisfaction. These findings suggest that enhancing students’ digital usage awareness and learning confidence can significantly improve learning outcomes in physical education courses. The article recommends that educators better utilize and refine digital resources in teaching and enhance students’ digital learning skills and awareness to improve the effectiveness of physical education teaching. This study enriches the content of the digital teaching model, reveals the intrinsic mechanisms of how digital resource learning affects learning outcomes, and provides new insights and methods for improving the teaching effectiveness of physical education courses.